Transgenerational associations between newborn metabolic profiles and bronchopulmonary dysplasia in neonates born to mothers with an obese phenotype - Jonathan D. Reiss; Wei Yang; Alan L. Chang; Jonathan Z. Long; Ivana Marić; Jochen Profit; Karl G. Sylvester; David K. Stevenson; Nima Aghaeepour; Gary M. Shaw (Scientific Reports)
Abstract Maternal obesity increases risk for bronchopulmonary dysplasia (BPD) by up to 42%. Identifying metabolic features that may contribute to the association between maternal pre-pregnancy body mass index (BMI) and BPD is critical in defining the molecular relationship between these conditions. We investigated the association between maternal obesity and BPD using newborn screen metabolites as an explanatory variable. We hypothesized that elevated pre-pregnancy BMI compared to a normal BMI referent group, is associated with increased circulating short and long-chain acylcarnitines and subsequent development of BPD. This was a retrospective study with linkage of maternal pre-pregnancy BMI, with newborn screen metabolites obtained from the California Newborn Screening Program and further linked with neonatal outcomes. Results demonstrated elevated levels of phenylalanine and proline associated with an increased risk for BPD (OR 5.3, 95% CI 1.2–23.8 and OR 5.4, 95% CI 1.3–22.3) in the obesity group compared to the referent group. Short- and long-chain acylcarnitines demonstrated a mildly increased risk for BPD in neonates of mothers with severe obesity compared to controls. The findings suggest that specific metabolites may influence the molecular conditioning that increases susceptibility to BPD.